Cultivating International Teachers Community of practice by Non-Formal Professional Development - Lazarinis, Fotis; Panagiotakopoulos, Theodor; Karatrantou, Anthi; Kameas, Achilles (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
Digitalisation of educational practices stands high on policy agendas at European and national levels. The COVID-19 pandemic caused the largest disruption of education in history having an impact on learners and trainers in all levels and types of education. This conjuncture greatly accelerated the digital transformation of all educational institutes requiring a transition to online learning models and tools (Liapis et al., 2022). However, the educational staff and particularly those that teach more theoretical topics do not necessarily have the appropriate ICT knowledge and skills to successfully support online training (Lazarinis et al., 2022, Panagiotakopoulos et al., 2021a; Iatrellis et al, 2021). Indeed, schoolteachers lack of digital skills is frequently reported in the literature as teachers are found to have insufficient capacity to develop learning activities with technological tools (Cruz and Diaz, 2016), while their skills readiness for online learning courses remains relatively low, especially regarding older teachers (Mirke et al., 2019; Capogna et. al., 2020). Aiming to address this gap, the RE-EDUCO project focuses on teacher training to improve their digital culture and skills for sharing new learning methodologies through innovative pedagogical approaches. Being part of a comprehensive work plan, the RE-EDUCO online training course for teachers aimed to address digital skills shortages and improve the capacities of the educational staff in effectively incorporating innovative online training approaches and tools in the teaching and learning process.